A comparative study on zinc fertilizer brands available in the markets of Jessore region - Islam, GMM; Tarafder, SK; Hasan, ABMM; Iqbal, SMA; Mamtaz, H (International Journal of Agricultural Research, Innovation and Technology, 2018)
A study was conducted in Monirampur upazila under Jessore district from July to December, 2016 to collect information on names, numbers and comparative availability of different brands of Zinc fertilizers in order to aid the assessment of nutrient status for quality of the brands. For this purpose, information was collected from 54 randomly selected fertilizer shops (20 BCIC fertilizer dealers and 34 retailers) through questionnaire interview. In the study total 77 brands [41 Zinc sulfate (mono), 11 Zinc sulfate (hepta) and 25 Chelated zinc] of zinc fertilizer marketed by 49 companies were found in the upazila. Zingsul, Mim zinc, Grogin, Bumper mono zinc, Eon zinc and Geel mono of Zinc sulfate (mono) brands, Topaz of Zinc sulfate (hepta) brands and Mim zinc gold of Chelated zinc brands were mostly available. “Grogin” of Zinc sulfate (mono) and “Topaz” of Zinc sulfate (hepta) were the top most available. Ten percent of Zinc sulfate (hepta) mentioned no registration number. There was a significant difference between highest and lowest MRP of all types (imported, supplied and manufactured) of Zinc sulfate (mono) and Zinc sulfate (hepta) fertilizer as well as imported Chelated zinc brands. Int. J. Agril. Res. Innov. & Tech. 7 (2): 57-62, December, 2017